Acute complicated type B aortic dissection during the New York City COVID‐19 surge - Ikeda, Shinichiro (J Card Surg, 2020)
The impact of the coronavirus disease 2019 (COVID‐19) pandemic in New York City (NYC) is dramatic. COVID‐19 cases surged, hospitals expanded to meet capacity, and NYC remains the global epicenter of this pandemic. During this unprecedented time, a young woman with known Marfan syndrome presented with an acute complicated type B aortic dissection to our Aortic Center. Using the provisional extension to induce a complete attachment technique, we treated this patient and quickly discharged her the next day to decrease the risk of COVID‐19 infection. Her progress was monitored using frequent phone calls and one office visit at two weeks.